تمويل التعليم في القطر العربي السوري في ظل العولمة - العمار رضوان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن العلاقة التي توضح درجة الترابط بين ظاهرة العولمة والنظام التعليمي تحتكم إلى معيار عملية التأثير والتأثر التي ينطلق منها النظام التربوي التعليمي، من خلال تفاعله مع البيئة المحلية في آن واحد. من هنا جاء التحليل في هذا البحث ليظهر مدى أهمية تمويل التعليم العالي والمشاكل التي تواجهه ومدى الحاجة إلى إيجاد مصادر تمويل جديدة غير المصادر الحكومية، نتيجة الحاجة الماسة للتمويل في قطاع التعليم العالي، نتيجة تزايد عدد الوافدين إلى الجامعات والمعاهد المتوسطة التي هي قضية حتمية في ظل مجتمع أصبحت نسبة الشباب فيه 42% من عدد السكان. وقد توصل الباحث إلى نتائج وتوصيات للاهتمام بعملية التمويل في المستقبل في مجال التعليم العالي، والتوسع في تشجيع القطاع الخاص ورجال الأعمال لدعم الجامعات والمعاهد والتوسع بأنظمة التعليم العالي التي تحقق إيراداً ذاتياً للجامعات الحكومية. The relation which explains the correlation degree between Globalization and the educational system appeals to the criterion of effect and influence from which the educational system starts, by its interaction with the local environment at the same time. The research focuses on the importance of financing higher education and its problems, and the extent of the need to find new sources other than the governmental ones. This is because there is a great need for financing in the higher education as a result of the increase in the number of students higher education institutions in a society whose youth makes 42% of the population. The researcher concluds with some results and recommendations calling for future financing in the sector of higher education and encouraging the private sector and business men to support the universities and intermediate institutes, and developing the laws of the higher education to give the governmental universities a private income.